español español: The exchange rate and the equilibrium interbank interest rate: determinants of the price and quotation index, 2000-2023 - Lopez Dominguez, Sergio Ivan (2023)
The Prices and Quotations Index (CPI) is an important element in the stock market activity within the Mexican market and abroad, since, with the issuance of it, it can generate attractiveness to invest in the Mexican stock market. The present research objective to determine if the variables exchange rate (TC), interbank interest rate of equilibrium 28 days (TIIE28) and the H1N1 pandemic, as a dummy variable, explain the behavior of the CPI, as well as under an empirical theoretical support. The period is from 2000-2023, with monthly data. To do this, the methodology to be followed was to apply growth rate to the variables to obtain stationarity; verify the unit root; using the econometric model of ordinary least squares (OLS) and; check the assumptions of linear regression (heteroscedasticity, autocorrelation and multicollinearity). The main econometric results are: the model is significant and stationary, so there are no unit roots; using the relevant techniques, compliance to the linear regression assumptions is checked. Finally, the conclusions that stand out are: the TC and TIIE28 are determinants for the CPI, since, as there is an increase, both in the TC and in the TIIE28, the CPI is reduced by percentage points.